Gastrointestinal Tuberculosis: An overview - Debi, Uma; Simran,; Singh, Lokesh; Sagar, Sathya; Sharma, Vishal; Bhatia, Vikas; Maralakunte, Muniraju; Sinha, Anindita; Devi, Gita; Prasad, Kaushal Kishor (Archives of Clinical and Medical Case Reports, 2020)
Tuberculosis has been one of the most common communicable diseases not only in India, but also world over. Abdomen is the most common extra-pulmonary site of the disease. It has been standard practice in the Indian subcontinent to consider tuberculosis as one of the differential diagnosis in most clinical scenarios, due to its high incidence and non-specificity of symptoms. It is imperative to be competent with a disease so prevalent. Radiological diagnosis goes a long way in proving or disproving a clinical diagnosis. One must always keep tuberculosis as a possible diagnosis and be familiar with various presentations of the disease.